Personal Branding Joko Widodo di Instagram Jelang Periode Akhir Kepresidenan - Dominika; Susilo, Daniel (Jurnal Komunikasi Profesional, 2024)
Personal branding has become an important concept in the digital era, especially for social media users. Social media platforms like Instagram provide individuals with the opportunity to shape and control their public image. President Joko Widodo, popularly known as Jokowi, is one of the Presidents of the Republic of Indonesia who actively uses Instagram to communicate with the public. This study employs a descriptive qualitative approach aimed at providing an overview of a communication phenomenon in a scientific context. Content analysis was conducted on the Instagram account @jokowi during the last year of his presidency, which will end in October 2024. This research illustrates how Jokowi utilizes Instagram as a tool to communicate and strengthen his personal branding. The findings show that Jokowi has fulfilled 8 key concepts of personal branding proposed by Peter Montoya, with 3 particularly dominant concepts: the law of specialization, the law of distinctiveness, and the law of personality. Despite his term nearing its end, Jokowi remains consistent in building his personal brand through Instagram, emphasizing leadership values, closeness to the people, and his achievements throughout his administration.